COMPARISON BETWEEN SIMULATION AND TRADITIONAL PEDAGOGIES EFFICACY AT ELEMENTARY LEVEL - Abdul Haque; Muhammad Kamran Abbasi; Ajab Ali Lashari (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper investigates students' performance, the difference between traditional teaching methods and simulation, and the correlation between conventional teaching methods and simulation. The experiment was done in the 7th class of Mubashir School of Excellence Taluka Qasimabad, District Hyderabad. It was an experimental study; students of the 7th class were equally divided into two groups: the experimental group and the control group. The sample consisted of 10 students. The duration of the study was two weeks. Pre and Post tests were conducted before and after the experiment. According to the findings of the study, it can be said that simulation is better than the traditional method of teaching, where students can enhance their knowledge and skills by doing practical networking in the Cisco Packet Tracer Simulator; students can find different types of switches, routers, cables and they can understand how a computer is connected with other computers, how they can send data from one computer to other on the same network. This study suggested to school teachers on behalf of this study that, as an alternative to lecture techniques, they should incorporate simulation into their teaching practice. This will significantly aid students in understanding their subjects. It is suggested to the school management on behalf of this study that you may use ICT for the students' better learning. This study suggests to the policymakers of the education department on behalf of this study if you provide ICT labs in your schools and include ICT in your curriculum as compulsory, our education system will rise and shine. According to this study, simulation is more efficient than traditional methods of teaching elementary-level students.